# SOLUTION: -(8y+3)-(-7y-4)=-3 Would this be correct -8y+3=7y-4=-3 My e-mail is collinscora@yahoo.com

Algebra ->  Algebra  -> College  -> Linear Algebra -> SOLUTION: -(8y+3)-(-7y-4)=-3 Would this be correct -8y+3=7y-4=-3 My e-mail is collinscora@yahoo.com      Log On

 Algebra: Linear Algebra (NOT Linear Equations) Solvers Lessons Answers archive Quiz In Depth

 Click here to see ALL problems on Linear Algebra Question 326829: -(8y+3)-(-7y-4)=-3 Would this be correct -8y+3=7y-4=-3 My e-mail is collinscora@yahoo.comAnswer by jessica43(140)   (Show Source): You can put this solution on YOUR website!This is not quite correct.... to solve this one, you first need to distribute the negatives and FOIL. -(8y+3) is the same as -1*(8y+3) So you need multiply each value in the parentheses by -1 and then add them: (-1)*(8y+3) = (-1)*(8y) + (-1)*(3) = -8y + (-3) = -8y - 3 You need to do the same for the rest of the problem: -(-7y-4)= (-1)*(-7y-4) = (-1)*(-7y) + (-1)*(-4) = 7y + 4 Now that you see how it is done in parts , let's do the whole thing: -(8y+3)-(-7y-4)=-3 ((-1)*(8y+3)) + ((-1)*(-7y-4)) = -3 (-8y - 3) + (7y + 4) = -3 -8y - 3 + 7y + 4 = -3 Now combine the like terms: -8y - 3 + 7y + 4 = -3 -y + 1 = -3 (-8y + 7y = -y; -3 + 4 = 1) -y = -4 y = 4 So your answer is y = 4.